Factors Influencing the Success of Toilet Training in Preschool-Aged Children - Nurherliyany, Metty; Sukmawati, Ima; Kusunawaty, Jajuk; Nuraplliani, Cindy (Genius Journal, 2024)
Introduction: Toilet training is defined as the ability to initiate and complete urination and defecation independently. This is an important marker in the normal development of children, as it is a challenging process not only for children but also for their families. Objective: The aim of this research is to find out what factors influence the success of toilet training among preschool children in the Karanganyar Village area. Methods: This research method is quantitative. The type of research used is correlational analytics with a cross-sectional approach. The population used in this research were 56 preschool-aged children in Karanganyar Village, Karangsiswa Kindergarten, Mahardika Kindergarten, and Terate PAUD, using total sampling techniques. Result: The results of this study show that, based on the chi square test, knowledge and work have a p value of <0.05, while education has a p value of >0.05. Conclusion: The conclusion is that there is an influence of mother's knowledge and work on the success of toilet training and there is no influence of education on the success of toilet training.